KUALITAS BETON DENGAN MEMANFAATKAN BOTTOM ASH LIMBAH BAHAN BAKAR BATU BARA PADA INDUSTRI - Irianta, F.X. Gunarsa (Jurnal Teknik Sipil dan Perencanaan, 2010)
Coal is used by large industries in Semarang and surroundings, for example Batam Tex, it is textile industry located in Ungaran. It needs coal for fuel  about 40 up to 50 tons per day. The blower of Batam Tex produces ± 2 up to 5 tons fly ash and bottom ash per day. Fly ash contains very smooth aggregate as black powder, and bottom ash contains small aggregate as black sand. Creating new innovation is important to be done. The amount of bottom ash waste needs to be researched and developed. The purpose of the research is to certain concrete straight strength by using bottom ash, with 3 variations of cement conten 280 kg, 300 kg, and 320 kg/m³ concrete. The result is the concrete strainght strength for each mixture and age 7, 14, 28 days are different. For the cement content 280 kg age 7 days the result is 60.12 kg/cm², age 14 days the result is 95.14 kg/cm², and age 28 days the result is 68.36 kg/cm². For the cement content 300 kg age 7 days the result is 62.91 kg/cm², age 14 days the result is 94.88 kg/cm², and age 28 days the result is 97.58 kg/cm². For the cement content 320 kg age 7 days the result is 152.43 kg/cm², age 14 days the result is 181.31 kg/cm², and age 28 days the result is 169.50 kg/cm². From the 3 mixtures, it is proved that the concrete age 28 days has desend straiht strength, so if the concrete is used for construction it needs more consideration.Di Semarang dan sekitarnya banyak terdapat industri-industri besar yang menggunakan bahan bakar batu bara, seperti industri tekstil ‘Batam Tek’ di Ungaran tiap hari membutuhkan batu bara sebagai bahan bakar 40 sampai 50 ton perhari. Dari mesin pembangkit uap (blower) dihasilkan limbah ± 2 sampai 5 ton per hari yang terdiri dari fly ash dan bottom ash. Fly ash berupa butiran sangat halus seperti tepung berwarna hitam, sedang bottom ash berupa butiran kecil-kecil seperti pasir. Penciptaan peluang baru yang kreatif dan inovatif perlu dilakukan, limbah bottom ash yang besar sudah selayaknya perlu dikaji dan dikembangkan. Kajian ini bertujuan menentukan kuat tekan beton menggunakan bottom ash, dengan 3 variasi kadar semen  = 280 kg, 300 kg dan 320 kg untuk tiap m³ beton.  Hasil pengujian bahwa kuat tekan beton bottom ash untuk tiap jenis campuran dan umur 7, 14 dan 28 hari berturut-turut 60.12 kg/cm²; 95.14 kg/cm² dan 68.36 kg/cm² untuk kadar semen 280 kg/m³ beton, 62.91 kg/cm²; 94.88 kg/cm² dan 97.58 kg/cm² untuk kadar semen 300 kg/m³ beton, 152.43 kg/cm²; 181.31 kg/cm² dan 169.50 kg/cm² untuk kadar semen 320 kg/m³ beton. Dari ketiga jenis campuran tersebut ternyata kuat tekan umur 28 hari mengalami penurunan, maka perlu dipertimbangkan bila beton dipakai untuk konstruksi.